Hana Hsu and the Ghost Crab Nation - Liu, Sylvia (Razorbill, 2022)
In a near future where most adults are connected to the multiweb through neural implants, a twelve-year-old uncovers a corporate plot to genetically manipulate her classmates, and her scientist mother may be involved in the conspiracy.